2004
DOI: 10.1002/chem.200305569
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous‐Solution Growth of GaP and InP Nanowires: A General Route to Phosphide, Oxide, Sulfide, and Tungstate Nanowires

Abstract: A general synthetic route has been developed for the growth of metal phosphide, oxide, sulfide, and tungstate nanowires in aqueous solution. In detail, cetyltrimethylammonium cations (CTA(+)) can be combined with anionic inorganic species along a co-condensation mechanism to form lamellar inorganic-surfactant intercalated mesostructures, which serve as both microreactors and reactants for the growth of nanowires. For example, GaP, InP, gamma-MnO(2), ZnO, SnS(2), ZnS, CdWO(4), and ZnWO(4) nanowires have been gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 39 publications
1
45
1
7
Order By: Relevance
“…The exact mechanism of luminescence is not clear at present and further study is under way. Previous reports had shown that InP nanostructures usually emitted red light [13,16,29,30]. However, the InP products prepared in our experiments can emit blue light, which is different from the previous reports and increases the potential applications of InP nanomaterial.…”
Section: Optical Propertycontrasting
confidence: 77%
See 1 more Smart Citation
“…The exact mechanism of luminescence is not clear at present and further study is under way. Previous reports had shown that InP nanostructures usually emitted red light [13,16,29,30]. However, the InP products prepared in our experiments can emit blue light, which is different from the previous reports and increases the potential applications of InP nanomaterial.…”
Section: Optical Propertycontrasting
confidence: 77%
“…Meanwhile, InP nanostructures can also be synthesized in solution systems. For instance, InP nanocrystals were obtained under ultrasonic irradiation from the reaction of InCl 3 ·4H 2 O, yellow phosphorus and KBH 4 in a mixed solvents of ethanol and benzene [14], monodispersed InP quantum dots were synthesized via the reaction between In 2 O 3 and yellow phosphorus in alkali aqueous [15], InP wires were prepared from the reaction of In 2 O 3 and yellow phosphorus with CTAB as surfactant in aqueous solution [16], InP nanocrystals with rod-like morphologies were obtained using InCl 3 ·4H 2 O, yellow phosphorus and NaBH 4 as reactants and employing C 17 H 35 CO 2 K as surfactant in aqueous ammonia [17]. However, the synthesis of InP 3D nanostructures such as hollow nanospheres, and flowerlike architectures has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, yellow phosphorus has been used with success, to produce InP NWs via PH 3 as an intermediate in an alkaline and pressurized environment, in a surfactant-templated system [75].…”
Section: (C) Solution-liquid-solid Synthesismentioning
confidence: 99%
“…Notably, solution synthesis has been widely used as one of the most effective approaches owing to the availability of flexible adjustment of the experimental parameters of the synthetic system [18][19][20][21][22]. Specifically, biomimetic or bio-inspired synthetic approach, which is easy, effective, and environmentally benign, has been recognized as a promising strategy for the fabrication of inorganic crystals with specific morphology and hierarchical architecture [23,24].…”
Section: Introductionmentioning
confidence: 99%